A systematic review of the current state of collaborative mixed reality technologies: 2013–2018 - Ryan Anthony J. de Belen; Huyen Nguyen; Daniel Filonik; Daniel Filonik; Tomasz Bednarz (AIMS Electronics and Electrical Engineering, 2019)
Over the last few decades, Mixed Reality (MR) interfaces have received great attention from academia and industry. Although a considerable amount of research has already been done to support collaboration between users in MR, there is still no systematic review to determine the current state of collaborative MR applications. In this paper, collaborative MR studies published from 2013 to 2018 were reviewed. A total of 259 papers have been categorised based on their application areas, types of display devices used, collaboration setups, and user interaction and experience aspects. The primary contribution of this paper is to present a high-level overview of collaborative MR influence across several research disciplines. The achievements from each application area are summarised. In addition, remarkable papers in their respective areas are highlighted. Among other things, our study finds that there are three complementary factors to support and enhance collaboration in MR environments: (i) annotation techniques, which provide non-verbal communication cues to users, (ii) cooperative object manipulation techniques, which divide complex 3D object manipulation process into simpler tasks between different users, and (iii) user perception and cognition studies, which aim to lessen cognitive workload for task understanding and completion, and to increase users’ perceptual awareness and presence. Finally, this paper identifies research gaps and future directions that can be useful for researchers who want to explore ways on how to foster collaboration between users and to develop collaborative applications in MR.